2011
DOI: 10.1029/2011eo380002
|View full text |Cite
|
Sign up to set email alerts
|

Using mobile phones to engage citizen scientists in research

Abstract: Mobile phone‐based tools have the potential to revolutionize the way citizen scientists are recruited and retained, facilitating a new type of “connected” citizen scientist—one who collects scientifically relevant data as part of his or her daily routine. Established citizen science programs collect information at local, regional, and continental scales to help answer diverse questions in the geosciences and environmental sciences. Hundreds of thousands of citizen scientists contribute to recurring research pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
59
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(65 citation statements)
references
References 0 publications
0
59
0
1
Order By: Relevance
“…Recent advances in digital information and communication technologies have enabled much wider participation in citizen science, to include people that may not possess any, or only limited, background knowledge of the studied subjects, but are nevertheless willing to contribute by collecting data (Adriaens et al 2015;Graham et al 2011;August et al 2015). Furthermore, the development of mobile smartphone technologies in particular offers several advantages, including the functionality to take photographs, use microphones and…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in digital information and communication technologies have enabled much wider participation in citizen science, to include people that may not possess any, or only limited, background knowledge of the studied subjects, but are nevertheless willing to contribute by collecting data (Adriaens et al 2015;Graham et al 2011;August et al 2015). Furthermore, the development of mobile smartphone technologies in particular offers several advantages, including the functionality to take photographs, use microphones and…”
Section: Introductionmentioning
confidence: 99%
“…It is, therefore, useful to also consider the use of other approaches to obtain water level data. Citizen science is now more frequently used to obtain environmental data over large areas (Savan et al, 2003;Bonney et al, 2009;Graham et al, 2011;Fohringer et al, 2015;Huddart et al, 2016;Wiseman and Bardsley, 2016). Little et al (2016) gave citizen scientists water level sounders to measure groundwater levels in private wells and found that these measurements provided valuable data on groundwater levels across a large area in Alberta, Canada, and that the measurements were relatively accurate; the root mean square error between citizen scientist observed water levels and pressure transducer based water levels ranged between 3 and 11 cm.…”
Section: Introductionmentioning
confidence: 99%
“…New technologies such as smartphone applications st (apps) are increasingly being made available and are used to involve citizens in the reporting of species in Europe (Graham et al 2011, Teacher et al 2013. Apps can support the generation of georeferenced records of IAS which, once validated, can complement professional monitoring schemes and return useful data for early warning, rapid response programs and management schemes .…”
Section: Introductionmentioning
confidence: 99%